Sobolev inequalities, the Poisson semigroup, and analysis on the sphere Sn. - Beckner, W (1992)
Hypercontractive estimates are obtained for the Poisson semigroup on Lp(Sn). Such estimates are determined by a sharp logarithmic Sobolev inequality that relates the entropy of a function on Sn to its smoothness.